2000
DOI: 10.1161/01.cir.102.16.1944
|View full text |Cite
|
Sign up to set email alerts
|

A Matrix Metalloproteinase Induction/Activation System Exists in the Human Left Ventricular Myocardium and Is Upregulated in Heart Failure

Abstract: Background-Matrix metalloproteinases (MMPs) contribute to matrix remodeling in disease states such as tumor metastases. Extracellular matrix metalloproteinase inducer (EMMPRIN) has been reported to increase MMP expression, and membrane-type MMP or MT1-MMP has been implicated to activate MMPs. The present study examined whether and to what degree EMMPRIN and MT1-MMP were expressed in human left ventricular (LV) myocardium as well as the association with MMP activity and expression in dilated cardiomyopathy (DCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
394
4
13

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(422 citation statements)
references
References 16 publications
11
394
4
13
Order By: Relevance
“…MMP-9 activity increases 1 day after MI, whereas MMP-2 activity starts to increase within 4 days after MI. Furthermore, MMP-9 abundance increases in both ischemic and non-ischemic dilated cardiomyopathy, whereas the abundance of MMP-2 increases only in non-ischemic dilated cardiomyopathy (9). These observations suggest differential regulation of MMP-2 and -9 in the heart.…”
mentioning
confidence: 78%
“…MMP-9 activity increases 1 day after MI, whereas MMP-2 activity starts to increase within 4 days after MI. Furthermore, MMP-9 abundance increases in both ischemic and non-ischemic dilated cardiomyopathy, whereas the abundance of MMP-2 increases only in non-ischemic dilated cardiomyopathy (9). These observations suggest differential regulation of MMP-2 and -9 in the heart.…”
mentioning
confidence: 78%
“…It is known that MMP-2 is able to degrade type IV collagen and is upregulated during heart failure. 14,24,25 Because we have shown changes in cardiomyocyte size and ECM volume after unloading of the LV by LVAD support 12,15 and given the close connection between type IV collagen and the cardiomyocyte, we hypothesized that the BM surrounding the cardiomyocyte must be reshaped when the cardiomyocytes become smaller by unloading of the heart by an LVAD. If so, MMP-2 (collagenase IV) can play a major role in this process of remodeling.…”
mentioning
confidence: 96%
“…Thus, a progressive activation of MMPs results in degradation of the fibrillar collagen matrix, and can lead to increased LV wall thinning and LV enlargement [15]. Recent clinical reports have demonstrated alterations in both myocardial and circulating activities of MMPs in patients with DCM [16][17][18]. Spinale et al [18] have reported a decreased myocardial activity of the interstitial collagenase, or MMP-1, which degrades the fibrillar collagen such as collagen types I and III, as well as increased activities of gelatinases, or MMP-2 and MMP-9, in DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical reports have demonstrated alterations in both myocardial and circulating activities of MMPs in patients with DCM [16][17][18]. Spinale et al [18] have reported a decreased myocardial activity of the interstitial collagenase, or MMP-1, which degrades the fibrillar collagen such as collagen types I and III, as well as increased activities of gelatinases, or MMP-2 and MMP-9, in DCM. This reduction in MMP-1 activity may result in an increased deposition of collagen types I and III.…”
Section: Discussionmentioning
confidence: 99%